2005
DOI: 10.1007/s00425-005-0186-8
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of ureidoglycolate in French bean (Phaseolus vulgaris) is catalysed by a ubiquitous ureidoglycolate urea-lyase

Abstract: A ureidoglycolate-degrading activity was analysed in different tissues of French bean (Phaseolus vulgaris L.) plants during development. Activity was detected in all the tissues analysed, although values were very low in seeds before germination and in cotyledons. After radicle emergence, the activity increased due to high activity present in the axes. The highest levels of specific activity were found in developing fruits, from which the enzyme was purified and characterised. This is the first ureidoglycolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
40
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 35 publications
0
40
0
Order By: Relevance
“…Especially controversial is the nature of the ureidoglycolate-degrading reaction. From chickpea (Cicer arietinum) and common bean (Phaseolus vulgaris), enzymes were purified that, in contrast to UAH, cleave ureidoglycolate to glyoxylate and urea (Muñoz et al, 2001(Muñoz et al, , 2006. Consistently, it was reported that in soybean, half of the nitrogen from allantoate was released as urea, presumably during ureidoglycolate degradation (Todd and Polacco, 2004).…”
mentioning
confidence: 81%
“…Especially controversial is the nature of the ureidoglycolate-degrading reaction. From chickpea (Cicer arietinum) and common bean (Phaseolus vulgaris), enzymes were purified that, in contrast to UAH, cleave ureidoglycolate to glyoxylate and urea (Muñoz et al, 2001(Muñoz et al, , 2006. Consistently, it was reported that in soybean, half of the nitrogen from allantoate was released as urea, presumably during ureidoglycolate degradation (Todd and Polacco, 2004).…”
mentioning
confidence: 81%
“…In contrast, a later study using soybean extracts indicated that one of two enzymes involved in allantoate breakdown does release urea (Todd and Polacco, 2004). In agreement with this, an enzyme releasing urea from ureidoglycolate (ureidoglycolate amidinohydrolase/urea lyase) was purified and biochemically characterized from chickpea (Cicer arietinum; Munoz et al, 2001) and French bean (Munoz et al, 2006). The yeast (Saccharomyces cerevisiae) dal2 mutant, lacking the fungal urea-releasing allantoate amidinohydrolase, could be complemented by the expression of an AAH candidate protein from Arabidopsis (Arabidopsis thaliana), called AtAAH ).…”
mentioning
confidence: 82%
“…In the shoot, ammonium is released from the ureides and is re-assimilated into amino acids. The enzymes involved in allantoate degradation in leguminous species have received special attention (Winkler et al, 1985(Winkler et al, , 1988Wells and Lees, 1991;Lukaszewski et al, 1992;Munoz et al, 2001Munoz et al, , 2006Todd and Polacco, 2004;Raso et al, 2007). Despite efforts for over two decades, an allantoate-degrading enzyme has never been fully purified from a plant, probably because the enzymatic activity was unstable (Lukaszewski et al, 1992;Raso et al, 2007).…”
mentioning
confidence: 99%
“…Inside the plant cells, urease hydrolyzes urea into ammonia, and the plant then uses it as a nitrogen source. In plants, urease is used to hydrolyze not only the urea acquired from the environment but also the urea that is internally produced by the plant through the catabolism of arginine and purines (Munoz et al 2006;Reinbothe and Mothes 1962;Todd and Polacco 2004). Of note, plant urease may also be involved in a defense mechanism against herbivores and microorganisms, which can explain its high abundance in seeds such as the soybean and jack bean (Goldraij et al 2003;Meyer-Bothling and Polacco 1987;Polacco and Winkler 1984;Stebbins et al 1991).…”
Section: Plant Ureasementioning
confidence: 99%